2023
DOI: 10.1038/s41467-023-39712-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of skin TRPV3 in temperature detection regulated by TMEM79 in mice

Abstract: TRPV3, a non-selective cation transient receptor potential (TRP) ion channel, is activated by warm temperatures. It is predominantly expressed in skin keratinocytes, and participates in various somatic processes. Previous studies have reported that thermosensation in mice lacking TRPV3 was impaired. Here, we identified a transmembrane protein, TMEM79, that acts as a negative regulator of TRPV3. Heterologous expression of TMEM79 was capable of suppressing TRPV3-mediated currents in HEK293T cells. In addition, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Our recent study further highlights a role for TRPV3 in skin pathophysiology. [ 5 ] As mentioned above, we reported that TMEM79 negatively regulates TRPV3 function in skin keratinocytes and concluded that TRPV3 indeed contributes to temperature sensing in mice. TMEM79 is a membrane protein with five transmembrane domains that is reported to be involved in skin barrier function.…”
Section: Trpv3 In Cutaneous Physiology and Pathophysiologymentioning
confidence: 68%
See 4 more Smart Citations
“…Our recent study further highlights a role for TRPV3 in skin pathophysiology. [ 5 ] As mentioned above, we reported that TMEM79 negatively regulates TRPV3 function in skin keratinocytes and concluded that TRPV3 indeed contributes to temperature sensing in mice. TMEM79 is a membrane protein with five transmembrane domains that is reported to be involved in skin barrier function.…”
Section: Trpv3 In Cutaneous Physiology and Pathophysiologymentioning
confidence: 68%
“…We recently used a Thermal Gradient Ring (TGR) having a narrower temperature range (10°C–45°C) to confirm that TRPV3 is indeed involved in warmth sensation by showing the indifference of mice to innocuous temperature. [ 5 ] In addition, we showed that TMEM79‐knockout mice prefer to stay at a bit higher optimal temperature than wild‐type mice likely due to increased TRPV3 levels on the plasma membrane, thus supporting a role for skin TRPV3 in thermosensation. [ 5 ] A recent commentary article raised several critical questions for future directions of TRPV3 warmth sensation research.…”
Section: Thermosensing Activity Of Trpv3mentioning
confidence: 84%
See 3 more Smart Citations